Inside Cover: Definitive Insight into the Graphite Oxide Reduction Mechanism by Deuterium Labeling (ChemPlusChem 9/2015). Issue 9 (September 2015) - Jankovský, Ondřej; Šimek, Petr; Luxa, Jan; Sedmidubský, David; Tomandl, Ivo; Macková, Anna; Mikšová, Romana; Malinský, Petr; Pumera, Martin; Sofer, Zdeněk
<x xml:space="preserve">Abstract</x> The cover picture shows graphite oxide (upper part) and its reduction in the solution containing complex hydrides (lower part). Deuterium labeling allowed clarification of the puzzling mechanism by proving that reduction was also accompanied by graphene hydrogenation. More details can be found in the Full Paper by Zdeněk Sofer et al. on page 1399 in Issue 9, 2015. (DOI: 10.1002/cctc.201500168).